Teachers’ Practices in Integrating Instructional Media into English Teaching in Elementary Classrooms - Yentri Anggeraini; Nopa Yusnilita; Nurul Afifah (Journal of English Language Learning, 2026)
Abstract: The integration of instructional media has become an important part of English teaching in elementary classrooms, particularly in supporting young learners who need engaging, interactive, and meaningful learning experiences. However, understanding how teachers integrate instructional media into daily classroom practices remains important, especially in contexts where teachers utilize various resources to support student learning. This study aims to explore teachers’ practices in integrating instructional media into elementary school teaching and to examine how these practices support students’ learning engagement and classroom participation. A qualitative case study design was employed at SD Negeri 123 OKU, Indonesia. The participants consisted of three elementary school teachers and students involved in the classroom activities. Data were collected through observations, a focus group discussion with the participating teachers, and document analysis of teaching modules. The collected data were analyzed using thematic analysis to identify patterns related to instructional media integration. The findings revealed that teachers utilized various instructional media, including visual media, audio-visual media, realia, and digital media such as LCD projectors, to support classroom instruction. The findings also indicated that instructional media encouraged students’ active participation through exploration, group activities, discussion, and hands-on learning experiences. However, the study also found that the effectiveness of instructional media depended on the selection of appropriate activities that matched young learners’ characteristics, particularly their need for interaction and movement during learning. This study highlights the importance of purposeful instructional media integration in creating engaging, meaningful, and student-centered learning environments in elementary education. The findings provide practical implications for English teachers in designing learning activities that effectively combine instructional media with appropriate pedagogical strategies.